How teachers apply effective speaking activities in order to increase student’s vocabulary and fluency at Rodolfo Rodriguez Alvarado ¨Los Quinchos¨ School from 3rd. Year Saturday program in the second semester 2019 - Cerna Castillo, Jenny Isabel | Ocón Martínez, María de los Angles | Canelo, Julio Cesar Canelo Julio Cesar (UNAN, Managua, 2020)
Nicaragua has experienced changes in Education in the last twenty years. While Spanish is the official language, the Ministry of Education has acknowledged that high school students have to gain even more proficiency in English. In the first place, globalization is exerting great pressure on most countries in this regard. For businesses to be competitive and thrive, professionals and knowledge workers in general, must know English. This has led to dramatic changes in how English teachers teach their learners, particularly the ability to speak the language. Even though the Ministry of Education has applied English in different levels, there are still significant challenges that we need to be overcome as a country. In this research, we want to determine how teachers applies effective speaking activities to improve the student’s fluency and vocabulary in the Rodolfo Rodriguez Alvarado ¨Los Quinchos¨ Institution. At the end of this report, we will explain and recommend strategies to overcome the difficulties that we might find in the teacher of ninth grade during the second semester of 2019, Saturdays program